DAMPAK LIMBAH PERTAMBANGAN BATUBARA SEBAGAI PENCEMAR LINGKUNGAN HIDUP DITINJAU DARI PASAL 22 UNDANG-UNDANG NOMOR 32 TAHUN 2009 DI KECAMATAN BATU SOPANG KABUPATEN PASER - Rudi Miharja (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
AbstractThe environment is formed by the activities undertaken by humans, changes can affect life and life, either directly or indirectly, environmental changes occur because no longer balanced organic composition or existing life because of spatial and development in Indonesia has been impressed still less integrated, tends to be fragmented with sectoral egoism and regional egoism.Mining activities in Indonesia in the decade is quite increasing, especially coal mining is often called black gold, this is due to the opening of a broader coal market yanag both domestic and foreign markets. Not infrequently the coal mining business results in the environmental impact of waste from coal mining, because the importance of the meaning of the environment itself for the life of the world raises awareness that strict and sustainable arrangement is needed in the rescue and pengalolaan environment both for short and long term.